2022
DOI: 10.1002/jctb.7053
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis chassis in biomanufacturing 4.0

Abstract: Synthetic biology, an emerging research field, can promote biomanufacturing 4.0 by offering various efficient chassis. Engineering Bacillus subtilis, a prominent workhorse in industrial biotechnology, through synthetic biology approaches may be a disruptive innovation. Diverse chassis forms are envisaged to deal with challenges in metabolic complexity, metabolic burden, and systems robustness. Thus, advancements in chassis engineering, a synthetic biology strategy for genome-reduced cell factories, cell-free s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…11 In addition, the gene knockout does not damage the growth of strains and still preserves their core cellular processes, such as DNA replication, cell division, and gene expression. 12,13 Escherichia coli is the preferred host cell for protein expression, with the advantages of simple culture conditions, high protein yield, and low culture cost. Hashimoto et al reported the largest reduction of E. coli genome based on MG1655 strain, and constructed the mutant ΔMG1655 with 29.7% genome deletion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, the gene knockout does not damage the growth of strains and still preserves their core cellular processes, such as DNA replication, cell division, and gene expression. 12,13 Escherichia coli is the preferred host cell for protein expression, with the advantages of simple culture conditions, high protein yield, and low culture cost. Hashimoto et al reported the largest reduction of E. coli genome based on MG1655 strain, and constructed the mutant ΔMG1655 with 29.7% genome deletion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…By eliminating nonessential genes, genome-reduced strains reduce unnecessary components, DNA fragments, and useless surface structures in the system . In addition, the gene knockout does not damage the growth of strains and still preserves their core cellular processes, such as DNA replication, cell division, and gene expression. , Escherichia coli is the preferred host cell for protein expression, with the advantages of simple culture conditions, high protein yield, and low culture cost. Hashimoto et al reported the largest reduction of E.…”
Section: Introductionmentioning
confidence: 99%